Mycology in the tropics updates on Philippine fungi - Guerrero, Jonathan Jaime G. (Developments in Microbiology., 2023)
"Mycology in the Tropics: Updates on Philippine Fungi comprehensively discusses the current state of Philippine mycology, including historical developments in the field, listings of fungi with diverse utilizations or applications, and those that cause economic impact on crop production in the country. Specifically, the chapters in the book introduce tropical mycology, describe different fungal groups, their biodiversity and conservation, and give insights into the applications of mycology in agriculture, health, industry and the environment. The book also includes quarantine regulations on economically important diseases and describes the importance of developing local studies on fungi."